La medida del pie romano: nota de crítica textual sobre un problema filológico-matemático de la "Repetitio Sexta de Mensuris" de Nebrija - Maestre Maestre, José María (2019)
The present article puts forth an important textual error of a philological and mathematical nature (the omission of the cardinal mille in the relative clause of the sentence“Cum quodque milliarium millenos passus habeat: qui conficiunt pedes quinque”) in the passageof the Repetitio sexta de mensuris (Salamanca, 1510) where Nebrija describes how he deter-mined the size of the Roman foot through the length of the miliaries of the Via de la Plata. The research is structured via a thorough internal study of Nebrija’s aforementioned opusculum, and it is based on Nebrija’s In Cosmographiae libros introductorium (Salamanca, 1503) and on the works of other Spanish humanists (Juan Ginés de Sepúlveda, Pedro de Esquivel and Pedro Rodríguez de Campomanes), which illustrate the work of our scholars in this field. The content of this work, in itself very important, is much more so since it deals with a discovery by Nebrija that the University of Salamanca exhibits to the public on the left wall next to the door of its Old Library, fulfilling thus a promise of the Andalusian humanist that he did not achieve.
Keywords: Nebrija, Antonio de, -- 1444-1522; Crítica textual; Romanos